2023
DOI: 10.21203/rs.3.rs-3147009/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hepatic ketogenesis regulates lipid homeostasis via ACSL1-mediated fatty acid partitioning

Sadeesh Ramakrishnan,
Raja Gopal Reddy Mooli,
Yerin Han
et al.

Abstract: Liver-derived ketone bodies play a crucial role in fasting energy homeostasis by fueling the brain and peripheral tissues. Ketogenesis also acts as a conduit to remove excess acetyl-CoA generated from fatty acid oxidation and protects against diet-induced hepatic steatosis. Surprisingly, no study has examined the role of ketogenesis in fasting-associated hepatocellular lipid metabolism. Ketogenesis is driven by the rate-limiting mitochondrial enzyme 3-hydroxymethylglutaryl CoA synthase (HMGCS2) abundantly expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…These findings suggest that ketogenesis might be linked to the lipidomic remodeling of the liver that occurs in MASLD-MASH. Though numerous studies have linked ketogenesis to MASLD-MASH 19,[71][72][73][74] , the underlying mechanisms and consequences remain unclear. Prior studies from our group and others demonstrated ketogenic insufficiency increases the susceptibility to MASLD-MASH by increasing hepatic oxidative fluxes and provoking a DNL metabolic and transcriptomic signature 24,75 .…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that ketogenesis might be linked to the lipidomic remodeling of the liver that occurs in MASLD-MASH. Though numerous studies have linked ketogenesis to MASLD-MASH 19,[71][72][73][74] , the underlying mechanisms and consequences remain unclear. Prior studies from our group and others demonstrated ketogenic insufficiency increases the susceptibility to MASLD-MASH by increasing hepatic oxidative fluxes and provoking a DNL metabolic and transcriptomic signature 24,75 .…”
Section: Discussionmentioning
confidence: 99%